Colonization of Subaltern Women in the Short Story “Qisshatu Fathiyyah Al-Misriyyah” - Avisena Perdana Putra Muama; Arif Mustofa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Discourse on literary criticism is currently widely read and studied in the academic world, especially about postcolonial. postcolonial studies provide a new perspective on modern era colonialism and its effects. Postcolonial offers disclosure of the conflicts of human life that occurred in the colonial era. However, in the real of literary studies, his postcolonial works are not only the period after colonialism ended, but works that have been written since they lasted until the present. This research is included in the type of qualitative research based on the library research methodology.The purpose of this study is to describe the forms of colonization that occurred to female characters as part of the subaltern group in the short story ''Qisshatu Fathiyyah Al-Misriyyah'' using a subaltern theory approach of Gayatri Spivak. The primary data sources were taken in the form of a short story entitled Qisshatu Fathiyyah Al-Misriyyah by Nawāl As-Sa’dāwī as well as some literature from articles and books that have a correlation with the research topic as a secondary source. The theory used is Gayatri Spivak's subaltern with a postcolonial study approach. The results of this study are in the form of colonization of subaltern women in the form of: (a) Early Marriage, (b) Physical Violence, (c) Marginalization, (d) Discrimination.